THE ROLE OF HOMEWORK IN THE SPIRITUAL DEVELOPMENT OF PRIMARY SCHOOL STUDENTS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article discusses the role of homework in the spiritual and moral upbringing of primary school students. The didactic potential of homework to improve the spiritual development of students is revealed.